Brum, Eliane (2024). La Amazonia: Viaje al centro del mundo - Bombana, Briana (Documents d’Anàlisi Geogràfica, 2025)
Brum, Eliane (2024) La Amazonia: Viaje al centro del mundo Barcelona: Miradas Salamandra, 432 p. ISBN 978-84-19456-39-7